Learning English for Specific Purposes via Moodle in Emergency Situations – The Students’ Perspective - Vidaković, Mirna M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper investigates the experiences and opinions of students who learnt English for specific purposes via Moodle in the period between March and June 2020. The aim was to analyse the extent and forms of their engagement in this type of learning, explore their perceived positive and negative aspects of the course, and obtain suggestions for integration of this educational platform into English language classes in future. In addition, the paper aimed to investigate if there were any statistically significant differences related to the respondents’ use of the platform and their participation in the course according to the level of their English language knowledge and digital competences. The sample comprised 107 students who completed an anonymous questionnaire. Quantitative and qualitative data were analysed using the descriptive statistics and content analysis. Kruskal-Wallis test was employed to detect the correlation between dependent and independent variables. The obtained results showed general satisfaction with the English language course run on Moodle, but also revealed the students’ observation that the platform should accompany face to face classes in order to make learning more effective. The positive and negative aspects of the course identified by respondents were mostly in line with the existing research within the field of emergency remote teaching. Students pointed to the advantages of learning English via Moodle in terms of flexibility, accessibility of teaching materials, functions of tools such as tests, glossaries, forums. They also highlighted drawbacks, such as absence of real-time communication, work overload, and lack of self-discipline. It was interesting to discover that although research participants recognized the benefits of communication and collaboration tools, they did not engage with them to the anticipated extent. The fact that the mentioned issue has been identified in online learning in general suggests that the cause might lie in traditional, teacher-centred approach to teaching, which is still widespread in the educational system in Serbia. The obtained data carry important pedagogical implications for both learners and teachers in terms of incorporating digital tools in classes and devising a strategy for implementation of remote teaching in times of crisis. Students should be acquainted more thoroughly with virtual educational environment, which would, in turn, lead to the increased engagement and development of learner autonomy. In order to achieve this goal, teachers should strive to enhance their technological and pedagogic competences. This would also help them keep pace with technological educational innovations and encounter potential future educational emergencies better prepared.
Keywords: emergency remote teaching; English for specific purposes; Moodle; higher education